Fluid collection in the retropharyngeal space: A wide spectrum of various emergency diseases. Issue 7 (July 2016) - Tomita, Hayato; Yamashiro, Tsuneo; Ikeda, Hirotaka; Fujikawa, Atsuko; Kurihara, Yoshiko; Nakajima, Yasuo
Highlights: This is the review to discuss fluid collections in the retropharyngeal space on CT and MRI. These conditions should be managed by different specialties. Some of the diseases require immediate surgical intervention to avoid life-threatening mediastinitis or airway obstruction. Radiologists must distinguish these diseases correctly and provide recommendations for their management to physicians. Abstract: Fluid collections in the retropharyngeal space (RPS) result from a wide spectrum of diseases, including retropharyngeal abscess, cervical osteomyelitis, and calcific tendinitis of the longus colli muscle. These conditions should be managed by different specialties; beginning with care in the emergency room, physicians from orthopedics, pediatrics, otolaryngology, and oncology are in charge of the treatment. Since these diseases demonstrate similar fluid collections in the RPS on computed tomography (CT) and magnetic resonance imaging (MRI), the radiologist's diagnosis based on the characteristic imaging findings is very important to identify the primary disease. Also, since some of the diseases require immediate surgical intervention to avoid life-threatening mediastinitis or airway obstruction, radiologists must distinguish these diseases correctly and provide recommendations for their management to physicians. Understanding clinical features and imaging findings of these fluid collections in the RPS is crucial for the best care.